2020
DOI: 10.1029/2019jg005012
|View full text |Cite
|
Sign up to set email alerts
|

Carbon System Simulation in the Pearl River Estuary, China: Mass Fluxes and Transformations

Abstract: A carbon cycle model is built to describe the behavior of carbon materials in the Pearl River Estuary (PRE), China. The distributions and transformations of dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), and particulate organic carbon (POC) are simulated in the water column and sediment for the year 2006. The terrestrial carbon input is the dominant factor that determines the seasonal variation of carbon, while physical and biochemical processes contribute to the spatial‐temporal circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 58 publications
(92 reference statements)
2
15
0
Order By: Relevance
“…The in situ data including salinity, temperature, nutrients, organic carbon, DO, pH and TA at different depths were collected by the State Oceanic Administration of China from July 15 to August 24, 2006 and from December 3, 2006 to January 20, 2007 in the PRE and its adjacent coastal area (Wang et al., 2017; H. Zhang & Li 2010). The carbon cycle component of our model has been extensively validated in previous studies (Liang et al., 2020; Ye et al., 2021), and the model skill in simulating key carbon cycle dynamics in PRE is comparable with the modeling studies conducted in other regions (Fitzpatrick, 2009; Kwiatkowski et al., 2014; Sohma et al., 2018). Therefore, this study focuses on the validation of the modeled distribution of DO, pH and TA.…”
Section: Resultssupporting
confidence: 72%
“…The in situ data including salinity, temperature, nutrients, organic carbon, DO, pH and TA at different depths were collected by the State Oceanic Administration of China from July 15 to August 24, 2006 and from December 3, 2006 to January 20, 2007 in the PRE and its adjacent coastal area (Wang et al., 2017; H. Zhang & Li 2010). The carbon cycle component of our model has been extensively validated in previous studies (Liang et al., 2020; Ye et al., 2021), and the model skill in simulating key carbon cycle dynamics in PRE is comparable with the modeling studies conducted in other regions (Fitzpatrick, 2009; Kwiatkowski et al., 2014; Sohma et al., 2018). Therefore, this study focuses on the validation of the modeled distribution of DO, pH and TA.…”
Section: Resultssupporting
confidence: 72%
“…The CO 2 emissions from the Dong River were higher in the wet season than in the dry season. This seasonal pattern is similar to that observed in the Xi and Daning rivers (Yao et al, 2007;Ni et al, 2019) but different from that observed in the Jinshui River in the upper Yangtze River, where pCO 2 is high in winter and low in summer (Luo et al, 2019), although all four rivers are in the East Asian Monsoon climate region. The seasonal differences in CO 2 emissions are largely caused by the pCO 2 variability, which in turn is regulated by external carbon inputs, internal production of CO 2 (Yao et al, 2007), and the dilution effect caused by precipitation (Johnson et al, 2007).…”
Section: A Comparison Of Co 2 Emissions To Other Riverssupporting
confidence: 68%
“…The seasonal differences in CO 2 emissions are largely caused by the pCO 2 variability, which in turn is regulated by external carbon inputs, internal production of CO 2 (Yao et al, 2007), and the dilution effect caused by precipitation (Johnson et al, 2007). For rivers where pCO 2 is lower in summer than in winter, the dilution effect overrides the effect of increased carbon inputs and internal CO 2 production (Luo et al, 2019). In contrast, for rivers like the Dong River, although the dilution effect remains, increased CO 2 inputs and metabolism are more significant factors in controlling its pCO 2 , thus leading to higher summer pCO 2 .…”
Section: A Comparison Of Co 2 Emissions To Other Riversmentioning
confidence: 99%
See 1 more Smart Citation
“…Viewing the entire PRE, Guo et al (2008) reported the seasonal variability of carbonate parameters in the main channel of the estuary based on field observations from 2000 to 2005; Liang et al (2020) simulated the spatial distributions of carbonate parameters in the summer and winter of 2006. In the hypoxic upper PRE, Guo et al (2008) found that both DIC and total alkalinity (TA) showed large seasonal variations, with much higher values in winter (>3000 µmol kg −1 ) than in summer (<1700 µmol kg −1 ).…”
Section: Introductionmentioning
confidence: 99%